“Aloe-heal coat” smart self-healing coating for anti-corrosion of automotive components - Juliawati, Alias; Fatin Ayuni, Ramlan; Nurul Amiratul, Johari; Nalliah, Nivishan; Abd Anasghaneem, Abd Aziz; Nasrul Azuan, Alang (2021)
“Aloe-Heal Coat” has been developed as a new smart coating as protection method to reduce corrosion severity of magnesium alloy components. Magnesium and its alloys have been used widely as the automotive components, such as BMW engine block, Jaguar seat frames, GM and Ford front cover, for vehicle weight reduction, but magnesium is highly susceptible to corrosion in most environments. Smart self-healing act with the presence of microcapsules corrosion inhibitor and epoxy coating that are formulated by ingredient of poly-urea formaldehyde (PUF), resorcinol, ammonium chloride, and polyvinyl alcohol as the shell for the microcapsules. Linseed oil, and aloe-vera extract were added as the secret ingredient for the corrosion inhibitors which is the core ingredient of the microcapsules.